2018
DOI: 10.1111/imcb.12029
|View full text |Cite
|
Sign up to set email alerts
|

MEK‐ERK signaling diametrically controls the stimulation of IL‐23p19 and EBI3 expression in epithelial cells by IL‐36γ

Abstract: Interleukin (IL)-36 cytokines are important regulators of mucosal homeostasis and inflammation. We previously established that oral epithelial cells strongly upregulate IL-36γ expression in response to the bacterial pathogen Porphyromonas gingivalis. Here, we have established that IL-36γ stimulates the expression of the IL-12 cytokine family members, IL-23p19 and Epstein-Barr Virus-Induced Gene 3 (EBI3), by oral epithelial cells; their expression was also selectively stimulated by IL-36α. Notably, IL-23p19 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 47 publications
1
13
0
Order By: Relevance
“…In fact, it has been reported that IL-17A regulates epidermal keratinocytes to produce chemokines such as CXCL1 and CXCL2 to induce neutrophils. In addition, it has also been reported that IL-39, which is a hetero dimer of IL-23p19 and EBI3, is downstream of IL-36γ and involved in the induction of neutrophils 30 . When IL-36Ra is lost, neutrophil-induced pathways, triggered by increased chemokines and IL-39, are further amplified through a positive feedback loop, which is consistent with the increase in neutrophils which we observed in our histopathological investigations.…”
Section: Discussionmentioning
confidence: 98%
“…In fact, it has been reported that IL-17A regulates epidermal keratinocytes to produce chemokines such as CXCL1 and CXCL2 to induce neutrophils. In addition, it has also been reported that IL-39, which is a hetero dimer of IL-23p19 and EBI3, is downstream of IL-36γ and involved in the induction of neutrophils 30 . When IL-36Ra is lost, neutrophil-induced pathways, triggered by increased chemokines and IL-39, are further amplified through a positive feedback loop, which is consistent with the increase in neutrophils which we observed in our histopathological investigations.…”
Section: Discussionmentioning
confidence: 98%
“…IL-36 cytokines are important regulators of mucosal homeostasis and inflammation. We recently established that oral epithelial cells selectively upregulate IL-36␥ in response to the bacterial pathogen P. gingivalis (24) and that IL-36␥ can stimulate oral epithelial cells to express inflammatory cytokines (24,26). Here, we have established that IL-36␥ also regulates the expression of antimicrobial proteins by oral epithelial cells, including the peptidoglycan amidase PGLYRP2.…”
Section: Discussionmentioning
confidence: 93%
“…Antimicrobial proteins and cytokines are important mediators of mucosal homeostasis and inflammation. We have previously shown that IL-36␥ regulates the expression of various inflammatory cytokines in oral epithelial cells (24,26). Thus, we sought to establish whether it also regulates the expression of antimicrobial proteins.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations